A Comparison of Isolation Stress and Unpredictable Chronic Mild Stress for the Establishment of Mouse Models of Depressive Disorder - Lee, Jin-Seok; Kang, Ji-Yun; Son, Chang-Gue (Frontiers in Behavioral Neuroscience, 2021)
This study aimed to help to understand the influence of stress on depression, which reflects the social environments of especially solitary life and the increasing prevalence of depressive disorders. In order to determine the distinguishable features of two-representative animal models of stress-induced depressive disorder, we compared isolation stress (IS) and unpredictable chronic mild stress (UCMS). After 4-week of stress, both models showed significant depressive- and anxiety-like behaviors in an open field test (OFT; p < 0.01 for IS, p < 0.01 for UCMS), forced swimming test (FST; p < 0.01 for IS, p < 0.01 for UCMS), and tail suspension test (TST; p < 0.01 for IS, p < 0.05 for UCMS) along with alterations in serum corticosterone levels, serotonin activity in the dorsal raphe nuclei and microglial activity in the dentate gyrus of the hippocampus (p < 0.05 for both parameters). In a comparison of the two stress models, IS strongly induced depressive and anxiety features, as indicated by all parameters: behavior test scores (p < 0.05 for OFT, FST and TST), serum corticosterone levels (p < 0.05), immunohistological alterations for serotonin activity (p < 0.05) and microglial activity (p = 0.072). Our results indicate the suitability of IS for the development of animal models of depressive disorders, and may reveal the medical impact of social isolation environment in modern society.